An epidemiological study on endoparasites of domestic rabbits (Oryctolagus cuniculus) in Egypt with special reference to their health impact - Elshahawy, Ismail; Elgoniemy, Ashraf (Penerbit Universiti Kebangsaan Malaysia, 2018)
The present study was designed to study the enteric parasites infection in domestic rabbits in Upper Egypt and its impact on their health. A total of 298 faecal samples were collected from different farms in Upper Egypt. Each faecal sample was screened for parasitic isolation during May 2011- October 2012. Furthermore, The Eimeria species from samples containing isolated and sporulated oocysts were morphologically identified under microscope. Additionally, the Sheather’s sugar flotation and Modified Zeihl Neelsen techniques were used to detect the Cryptosporidium species oocyst. According to results of the present study, the overall enteric parasite infections in rabbits was 68.12%, with 5.7% samples were found to be positive for helminths (P. ambiguus) and 49% were found to harbour various species of protozoa (Eimeria spp. and Cryptosporidium oocysts). Influences of age, sex and breed on the prevalence were recorded. Also, there was strong significant seasonal trends in the prevalence of the recovered parasites. Eight species of Eimeria were detected. Concurrent infection with two to eight Eimeria species occurred most frequently. Cryptosporidium oocyst was detected in 45 rabbits (15.1%). To the best of author’s knowledge, this the first report of E. piriformis and Cryptosporidium species in rabbits in Egypt. Histopathological changes were indicative of inflammatory reactions brought about by parasitic infection with Eimeria species and its consequent irritating effects on intestine. The current study showed the characteristics of the prevalence of rabbit enteric parasite infection in Egypt and provided relevant ‘baseline’ data for assessing the effectiveness of future control strategies against these parasites in Egypt.